Supply Chain Risk Management Approaches Under Different Conditions of Risk. Issue 3 (21st August 2014) - Manuj, Ila; Esper, Terry L.; Stank, Theodore P.
<x xml:space="preserve">Abstract</x> A recent Deloitte study of 600 Supply Chain and C‐Level executives revealed that 45% felt that their supply chain risk management programs were only somewhat effective or not effective at all, while a mere 33% used risk management approaches to proactively and strategically manage supply chain risk based on conditions in their operating environment. Using a two‐method approach, the research summarized in this paper investigates the effectiveness of different supply chain risk management approaches by examining how performance varies when these approaches are applied under different risk conditions. The results counter prevailing knowledge regarding the appropriate use of such widely acknowledged risk management approaches as postponement and speculation, and highlight the dangers of functionally isolated decision making. The results lend credence to increasing calls for interdisciplinary research to address broad‐based supply and demand chain problems, and support the need to utilize performance metrics such as net profit to accurately assess supply chain decisions.